2019
DOI: 10.29359/bjhpa.11.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The relation between selected anthropometric variables and the sports results of early pubescent swimmers

Abstract: Background: Relations between anthropometric parameters and sports results in swimming are well documented, but only few studies concern young athletes. Scientific evidence do not indicate definitely, which anthropometric variables determine swimming performance among pubertal athletes. Material and methods: Forty one swimmers at the mean age of 12.2 years (including 15 females) were examined. Body composition was assessed by Tanita BC 545N device. Body height, hand length, hand width and arm span were also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…All the female soccer players were having relatively the same chest girth and mean finger span. The probable implication for this equality could be that the players had identical advantages in activities related to chest girth in soccer playing such as trapping the ball with the chest, blocking the opponent, and front charging which agreed with earlier studies [30][31][32] but less than average individual which is required for female soccer game as stipulated [19,20]. Female Universities Soccer Players in Ghana…”
Section: Discussionsupporting
confidence: 80%
“…All the female soccer players were having relatively the same chest girth and mean finger span. The probable implication for this equality could be that the players had identical advantages in activities related to chest girth in soccer playing such as trapping the ball with the chest, blocking the opponent, and front charging which agreed with earlier studies [30][31][32] but less than average individual which is required for female soccer game as stipulated [19,20]. Female Universities Soccer Players in Ghana…”
Section: Discussionsupporting
confidence: 80%
“…Researchers are prone to assess the anthropometrics of young swimmers of both sexes, because these features play one of the major roles in the swimming performance, kinematics, energetics, and efficiency (Geladas et al, 2005 ; Jürimäe et al, 2007 ; Lätt et al, 2009a ), in addition to hydrodynamics (Kjendlie and Stallman, 2008 ; Barbosa et al, 2014 ). Cross-sectional studies showed that variables such as height (H), arm span (AS), and hand length (HL) are strongly and positively correlated to Freestyle sprint performance (i.e., 50 or 100 m) (Geladas et al, 2005 ; Morais et al, 2012 ; Bielec and Jurak, 2019 ). The same trend was verified in breaststroke, in which swimmers with longer upper-limb lengths and wider girths had a significant advantage (i.e., better performance in the 100 m) (Sammoud et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On a sample of 12-year-old swimmers, Geladas et al (2005), found significant correlations between competitive performance in the 100 m crawl in boys with body mass (r=0.65), chest circumference (r=0.61), arm span (r=0.64), body vision (r=0.61), biacromial diameter (r=0.61), biiliac diameter (r=0.46) and in girls with body height (r=0.31), arm span (r=0.30), but no significant correlations were found with the amount of subcutaneous fat in either boys or girls. Bielec et al (2019), in their research determined a significant correlation between the results of the 50 m crawl and body height (r=0.60), arm length (r=0.52), arm span (r=0.52) in girls of early puberty age (12.1 ± 0.5). In the study of Lat et al (2010), anthropometrical factors explain 45 % of the variance in 100 m swimming performance on the 25 adolescent male swimmers (15.2 ± 1.9 years).…”
Section: Introductionmentioning
confidence: 89%
“…Research has established that certain morphological characteristics are significantly related to competitive performance in swimming (Jürimäe et al, 2007;Senel et al, 2017). Significant correlations between anthropometric indicators and competitive results among swimmers were recorded in the studies of many authors (Keskinen et al, 1989;Pelayo et al, 1996;Strazala et al, 2005;Jürimäe et al, 2007, Bielec et al, 2019. On a sample of 12-year-old swimmers, Geladas et al (2005), found significant correlations between competitive performance in the 100 m crawl in boys with body mass (r=0.65), chest circumference (r=0.61), arm span (r=0.64), body vision (r=0.61), biacromial diameter (r=0.61), biiliac diameter (r=0.46) and in girls with body height (r=0.31), arm span (r=0.30), but no significant correlations were found with the amount of subcutaneous fat in either boys or girls.…”
Section: Introductionmentioning
confidence: 99%